‘How long do you think tt’s gonna ast?': the Velvet Underground, The Doors, Bob Dylan and the 1960s rock counterculture - Strongman, Alexander (2021)
The 1960s rock counterculture is typically seen by journalists and fans in terms of overly simplistic or mythologised histories. These histories have become, to an extent, part of the cultural legacy of the 1960s and the means by which we understand that countercultural movement. However, by closely examining the primary source material of three of the period’s most influential artists, this thesis uncovers the nuanced, diverse and contradictory nature of the 1960s rock counterculture. This thesis examines key songs by The Velvet Underground, The Doors and Bob Dylan. Through close analysis of both music, lyrics and performance, I will interrogate the interplay between them as expressions of the cultural and political ideals of each artist. This approach facilitates a deeper understanding of how each group relates to the 1960s rock counterculture and wider 1960s counterculture. It is also a departure from the typical scholarly reliance on analysis of lyrics, especially in analyses of The Doors and Bob Dylan. Secondly, this approach will broaden the current understanding and definitions of 1960s’ rock counterculture by allowing the primary source material to illustrate each artist’s position within it. By uncovering this complex history of the 1960s rock counterculture we will uncover how sociological definitions of ‘counterculture’ are formulated within 1960s rock music, and more closely examine the complex interplay of bands within it. This helps us to navigate the complicated history of the wider 1960s counterculture; to illustrate its nuance in 1960s rock music and move away from mythologised journalistic narratives.